Elaboración de una guía multimedia de ilustración a lápiz y carboncillo con técnicas básicas y avanzadas, para fomentar el interés en el dibujo artístico en los estudiantes de la carrera de diseño gráfico de la Universidad Técnica de Cotopaxi en el periodo 2014 - Molina Gordillo, Telmo Efraín (2015)
The present investigation research was done keeping on mind that in this society a high level of education is required, which demands that teaching adjusts to the necessity to train professionals with a high level of knowledge and skills. From this starts the idea to do this investigation project to get the students of graphic design keep interest in artistic design, to develop this skill, helps with the development of creativity, innovation, invention, knowledge of composition, volume, shape, perspective and chromatic. All the mentioned before are part of the essential knowledge that a good graphic designer must have....